DECENTRALISATION AND EDUCATION FOR ALL IN INDONESIA - Richard Richy Kuhon (Polyglot, 2020)
The discourse on decentralisation in developing countries is seen as a strategy in restructuring and improving economic, social and public welfare including the education sector. This idea is fundamentally in line with the goals of Education for All (EFA). The experience of Indonesia that had shifted from a strongly centralised system to a decentralised one in the early 2000s provides an interesting case. This article argues that the current decentralised system in education has seen an insignificant effect in achieving EFA. Through an extensive literature study, this article draws attention to the  particular concerns of human resources, curriculum, corruption and poverty issues as contributing factors to the seemingly failing efforts in the decentralised settings, all in the light of Indonesia's historical development.